Social Constructivism: Principles and Implications to Mathematics Learning - Mangwende, Edmore (Universitas Muhammadiyah Surakarta, 2026)
This paper examines social constructivism as a learning theory and its implications in mathematics learning. The study followed a conceptual qualitative paradigm. The researcher used secondary data obtained from journal articles, e-books, periodicals and websites. Social constructivism emphasizes active construction of knowledge by learners through interaction with others and the environment. According to the theory, the learner understands the world through experiencing it. Reality is socially constructed and it depends on individual interpretation. In mathematics learning, the theory implies that mathematics tasks make sense to the learners if they solve real life problems. Mathematics learners should not simply memorise concepts, but should critically analyse their own and other people’s mathematical perspectives. More marks should be awarded for the thought process than for the final solution to a mathematical task. Mathematics learning should be taken beyond the classroom. Formal mathematics learning can be built atop the knowledge gained by the learners through culturally performed tasks. The mathematics learners should view their teacher as a facilitator, co-learner, co-explorer and co-constructor of knowledge. Teaching strategies that promote collaboration and active participation of learners are desirable. Peer and self assessment help to foster active and interactive mathematics learning.